Development of Calculus Learning Videos as Learning Mitigation Efforts During Covid-19 Pandemic - Achmad Fauzan; Sekti Kartika Dini; Rohmatul Fajriyah; Novendri Isra Asriny; Sheilta Alphenia; Riefyal Arshyzha Mustain (Universitas Swadaya Gunung Djati, 2022)
This research is focused on learning media in the form of asynchronous videos as a learning mitigation effort during the Covid-19 pandemic for Calculus 1 subject. The objectives of this study were tevaluate the learning media provided during the Covid-19 pandemic. The data sources used are primary data from Final Exam (FE) scores before the pandemic (academic year 2018/2019 and 2019/2020) and during the pandemic (academic year 2020/2021), as well as questionnaires distributed to students. The analytical methods used are Kruskal Wallis test, Mann-Whitney test, Importance-performance analysis (IPA), and text mining. The results showed that there were differences in FE scores for each academic year. The highest average and median scores of FE are in the 2020/2021 academic year. This shows that the online learning method through videos in the Calculus I subject for the 2020/2021 academic year has succeeded in increasing scores of FE student. Based on the results of IPA, the average value of the Customer Satisfaction Index (CSI) is 97.97%, with details of 50% on priority achievement, 33.33% on top priority, and 16.67% on low priority. The results of text mining related to learning media show that the videos provided are easy to understand, interesting, and clear in explaining the material.